Islamic bank efficiency: an efficiency method with SFA - Fajra Octrina; Hariadi Eka Priatmojo (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
Judging from the financial ratios, the performance of Islamic banking in Indonesia was remarkably stable both before and during the Covid-19 pandemic. However, another thing is whether this condition could make Islamic banks continue to work effectively. This study aimed to measure the cost efficiency of Islamic commercial banks in Indonesia quarter I of 2019 – quarter IV of 2020 and analyze the influencing factors in cost efficiency. The study used a saturated sampling technique with a total sample of 14 Islamic commercial banks, while the efficiency level was determined using the Stochastic Frontier Analysis (SFA) method. It turns out that PT. Bank Muamalat Indonesia Tbk. has the highest efficiency value of 0.9284. Several banks with an efficiency value of more than 0.5 are PT. Bank Aceh Syariah, PT. Bank BNI Syariah, and PT. Bank Mega Syariah. In this study, only inflation variables affect efficiency. In contrast, bank size, Return on Assets (ROA), Net Operating Margin (NOM), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR) variables, Capital Adequacy Ratio (CAR), Gross Domestic Product (GDP), and the rupiah exchange rate don’t affect the efficiency. Overall, all the company's internal variables and environmental variables affect efficiency.